CITRA DIRI TOKOH HIME DALAM DONGENG KAGUYA HIME, KAMI NAGA HIME, DAN HACHI KATSUGI HIME - Nyoman, Ayu Tri Yuliasari (Humanis; Volume 12. No.2. Agustus 2015, 2015)
Fairy tale of Kaguya Hime, Kami Naga Hime, and Hachi Katsugi Hime selected as the data source because there three fairy tales describe the characteristics of women (Hime) of the Heian period, Nara, and Edo. The story of Kaguya Hime, Kami Naga Hime, and Hachi Katsugi Hime is in the book entitled Nihon Mukashi Banashi written by Kawauchi Sayumi. The theory used is a woman imaging theory by Sugihastuti and the theory of functionalism folklore by William R. Bascom. The analysis showed similarities of Hime character portrayal in the Heian period, Nara and Edo. It can be seen from the makeup, and long black hair. Psychological state of Hime also figures also affect the social life in society and in the family environment. In addition, through a fairy tale of Kaguya Hime, Kami Naga Hime and Hachi Katsugi Hime can be know that the most prominent function of fairy tales in there three fairy tale is as a and have children's education namely to teach children to share in return, to become a diligent prayer, and have tolerance.
Keywords: self-image of women, Hime, Japanese fairy tales